GENERAL DESCRIPTION OF THE FAMILY LAMIACEAE. THEIR CATEGORIES AND TYPES - Axmatova , Dilyora Ravshanbek qizi (Educational Research in Universal Sciences, 2023)
The article provides information about the morphology, regions of distribution, and life forms of species belonging to the family of mints (Lamiaceae) distributed in Uzbekistan.